Efficient and Mild Cyclization Procedures for the Synthesis of 1,2-dihydropyridine-3,5-dicarbonitrile and Ethyl 4H-pyran-2-carboxylate Derivatives Catalyzed by DABCO in Aqueous Media - Moloudi, Maryam; Kabirifard, Hassan; Olia Lavasani, Amirhosein S. (Current Organocatalysis, 2018)
Background: A facile, effective and green methodology has been developed for the synthesis of 1,2-dihydropyridine-3,5-dicarbonitriles (3a-h) and ethyl 4H-pyran-2-carboxylates (5a-d) through one-pot, two or three-component condensation reactions consisting of aromatic aldehydes, malononitrile and cyanoacetic acid hydrazide or ethyl benzoylpyruvate in the presence of 1,4-diazabicyclo [2.2.2]octane, DABCO, in aqueous ethanol at room temperature. This work consistently has advantages as high yields, short reaction times, mild reaction condition, simple procedure and low toxicity. Methods: To a solution of arylaldehydes (1.0 mmol) and malononitrile (1.0 mmol) DABCO (20 mol%) H2O/EtOH (1:1, 10 mL) were added. The mixture was stirred for 15 min then cyanoacetic acid hydrazide or ethyl benzoylpyruvate (1.0 mmol) was added to the mixture. The mixture was stirred at ambient temperature for 90-120 min (the progress of the reaction being monitored by TLC and using hexane/AcOEt 1:1 as an eluent). The resulting solid was filtered, washed with cold H2O for removal of the catalyst, then crystallized from EtOH. All of the resulting structures were confirmed by their physical constant, IR, 1H NMR, 13C NMR spectroscopy and elemental analyses. Results: Convenient and practical protocols to 1,2-dihydropyridine-3,5-dicarbonitriles (3a-h) and 4Hpyran- 2-carboxylates (5a-d) from aromatic aldehydes, malononitrile and cyanoacetic acid hydrazide or ethyl benzoylpyruvate using DABCO as an efficient catalyst are described. Conclusion: In conclusion, we have presented DABCO as a mild and efficient catalyst for the synthesis of the corresponding 1,2-dihydropyridine-3,5-dicarbonitriles (3a-h) and 4H-pyran-2-carboxylates (5a-d). DABCO is inexpensive, nontoxic, easy to handle, and can act as a green medium. Simple work-up procedure, short reaction times, excellent yields of product with better purity, green solvent and mild condition are advantages of this protocol.
Keywords: aromatic aldehyde